METHODS OF PROJECT-VECTOR MANAGEMENT OF EDUCATIONAL ENVIRONMENTS - А. Biloshchytskyi (Astana IT University, 2021)
Based on the developed mathematical model of the project-vector space, the methods of determining the endpoints of the objects of the project-vector space (PVS) and the calculation of the trajectory of the movement to these points are proposed. It is shown that the problem of developing these methods is related to the definition of such projects (project integration), which will correspond to the maximum expansion of “Universal Projects” educational environment. Calculation of the trajectory of the movement in the project-vector space ensures the achievement of the objectives of the project with minimal time and financial resources. It is proposed to use the Monte Carlo method to calculate the options for the trajectory of PVS subjects. This distribution of probabilities when choosing the displacement of objects and subjects of PVS corresponds to the priority of subjects and the impact of objects on the displacement of these subjects. For the assessment of the magnitude of the impact on the movement of PVS subjects it was developed the structure of the expert table and the model of the calculation of the average expert assessment of such an impact. Implementation of the given methods will allow to dynamically evaluate the most important goals for all interested parties of the project, as well as to develop ways to achieve them in real terms. In this case, the real conditions of the projects are described in the system of impact on the movement of objects and subjects of PVS in the expanding “Universal Projects”.